(3cJGH CQSWhNS aj LQ ef GdfjQjf hHYOjgeGs - (3GQSWQNSs
(3ChdgG (B:s
(3aEf bOQ GdCQV YfO Pdc GdeQHY bOQ GdeQcR hGdfbWI s
(3BNQgG (B:s
(3Je cJGH CQSWQNS ai LQeI GdfjJQjf hHYOjgeG s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdKGdK YTQs
(3HgG CTcGd gfOSjIs
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1409s
(3eUOQ GbJfGA GdCUd (B:s
(3LGeYI jhJG s
Keywords: (3Gdadcs